ONCOPHORA FOTEDARI (UBPUBLISHED MASOODI, 1987) DESCRIBED FROM THE INTESTINE OF MARINE FISH TACHURUS ARIUS AT CALICUT KERALA, INDIA RECORDED AS A NEW HOST - BEGUM, IRFANA; GUPTA, P.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Oncophora fotedari (unpublished form Masoodi, 1987) is redescribed from the intestine of a marine fish Tachiurus arius at Calicut, Kerala, India and recorded as a new host. The Present specimen having close resemblance with Ofotedari, Masoodi, 1987 in the presence of citinous buccal capsule; comb like structure in buccal capsule, tridents, single spicule and absence of gubernaculam. However, differs from it in having three rows of spine in buccal capsule instead of one or two and eight pairs of caudal papillae (six pairs preanal and two pairs postanal) instead of five pairs (three pairs preanal and two pairs postanal) and size of various body organs. These variations are considered as intraspecific variations.